Predictive Value of Nasal Nitric Oxide and Serum NOS2 Levels in the Efficacy of Subcutaneous Immunotherapy in Pediatric Patients with Allergic Rhinitis - Sihui Wen; Shenghao Cheng; Shaobing Xie; Hua Zhang; Junyi Zhang; Fengjun Wang; Shumin Xie; Zhihai Xie; Weihong Jiang (Hindawi Limited, 2022)
Background. Subcutaneous immunotherapy (SCIT) is an effective therapy for allergic rhinitis (AR), but some AR patients still do not benefit from it. Nasal nitric oxide (nNO) and inducible nitric oxide synthase (iNOS/NOS2) act important roles in AR. This study aims to explore the abilities of serum NOS2 and nNO in predicting the clinical efficacy of SCIT in AR patients. Methods. We recruited 40 healthy controls (HCs) and 120 AR patients in this study. Serum NOS2 and nNO levels were compared between the two groups. In the AR group, patients underwent and finished 1-year of SCIT, and divided into the effective and ineffective groups, and the relationships between serum NOS2 and nNO levels and efficacy of SCIT were evaluated. Results. The serum NOS2 and nNO levels were higher in AR patients than HCs. In the effective group, the serum NOS2 and nNO levels were increased than the ineffective group. ROC curves presented that a combination of serum NOS2 and nNO exhibited promising predictive ability in predicting the clinical efficacy of SCIT. Conclusions. Serum NOS2 and nNO levels were enhanced in AR patients and might affect the efficacy of SCIT. The combined use of serum NOS2 and nNO levels could be a reliable and useful method for predicting the clinical efficacy of SCIT.